Gastritis cystica profunda with predominant histiocytic reaction mimicking solid submucosal tumor - Noh, Sang Jae; Kim, Kyoung Min; Jang, Kyu Yun (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Noh SJ, Kim KM, Jang KY. Gastritis cystica profunda with predominant histiocytic reaction mimicking solid submucosal tumor. Turk J Gastroenterol 2020; 31(10): 726-8.